Characteristics, management and changing incidence of children with empyema in a paediatric intensive care unit. (22nd February 2022) - Subhi, Rami; Gelbart, Ben; Ching, Natasha; Thompson, Jenny; Osowicki, Joshua; Rozen, Thomas H; Shanthikumar, Shivanthan; Teague, Warwick; Duke, Trevor
Abstract : Aim: Paediatric intensive care unit (PICU) admissions for empyema increased following the 13‐valent pneumococcal conjugate vaccine (PCV13). We describe the clinical characteristics, management and outcomes for children with empyema and compare incidence before and after PCV13. Methods: Retrospective study of patients <18 years admitted to The Royal Children's Hospital Melbourne PICU with empyema between January 2016 and July 2019. We investigated the incidence of empyema during two time periods: 2007–2010 (pre‐PCV13) and 2016–2019 (post‐PCV13). Results: Seventy‐one children (1.9% of all PICU admissions) were admitted to PICU with empyema between 2016 and 2019. Sixty‐one (86%) had unilateral disease, 11 (16%) presented with shock and 44 (62%) were ventilated. Streptococcus pneumoniae and group A Streptococcus were the most commonly identified pathogens. Forty‐five (63%) were managed with video‐assisted thoracoscopic surgery (VATS). There was a 31% reduction in empyema hospitalisations as a proportion of all hospitalisations (IRR 0.69, 95% CI 0.59–0.8), but a 2.8‐fold increase in empyema PICU admissions as a proportion of all PICU admissions (95% CI 2.2–3.5, P < 0.001). For the PICU cohort, this was accompanied by reduction in PIM2 probability of death (median 1% vs. 1.9%, P = 0.02) and duration of intubation (median 69 h vs. 126.5 h, P = 0.045). Conclusions: In children with empyema in PICU 62% required ventilation, 16% had features of shock and 63% received VATS. Empyema admissions, as a proportion of all PICU admissions, increased in the era post‐PCV13 compared to pre‐PCV13 despite no increase in illness severity at admission.